0586 Extending Sleep in Short Sleeping Middle-aged Adults at Risk for the Metabolic Syndrome. (25th May 2022) - Malone, Susan; Patterson, Freda; Hoopes, Elissa; Wong, Agnes; Grunin, Laura; Yu, Gary; Dickson, Victoria; Melkus, Gail
Abstract: Introduction: Short sleep predicts the metabolic syndrome (MetS). Extending sleep improves certain MetS factors, specifically insulin sensitivity and blood pressure in adults without MetS. The absence of sleep intervention studies in community-dwelling adults with MetS limits progress in advancing sleep extension interventions to this subgroup. This study evaluated the feasibility, acceptability, and impact on End-of-Treatment (EOT) sleep outcomes of a 12-week sleep intervention. Methods: Middle aged adults who were short sleepers and at risk for METs participated in a single-arm 12-week, 12-session sleep intervention based on cognitive behavioral therapy for insomnia delivered via videoconferencing platform. Feasibility and acceptability were assessed using retention and attendance rates as well as mean sleep diary completions (≥4 diaries/week). Anticipated (baseline) and experienced (EOT) acceptability were assessed using a 16-item survey that estimated self-reported acceptability, feasibility, perceived benefit, satisfaction, and overall satisfaction. Sleep was estimated from baseline and EOT 2-week wrist actigraphy data. Daytime sleepiness was assessed using the Epworth Sleepiness Scale. Paired sample t-tests modeled changes in acceptability, feasibility, perceived benefit, satisfaction, overall satisfaction, sleep and daytime sleepiness from baseline to EOT. Results: The intent-to-treat sample included 44 adults (mean age 52y, 59% female, 41% Black, 48% White, 11% Other, 82% non-Hispanic). Three participants withdrew leaving N=41 (retention rate=93%). Eighty-six percent attended >80% of sessions and mean sleep diary completion was 6.7 diaries/week. There were statistically significant changes in self-reported anticipated (baseline) and experienced (EOT) acceptability surveys indicating greater EOT acceptability (p<0.001), perceived benefit (p<0.001), satisfaction (p<0.001), and overall evaluation (p<0.001). Statistically significant improvements in sleep from baseline to EOT included increased time-in-bed (Mbaseline=6.00h SD= 0.68h – MEOT=7.48, SD= 1.21; p<0.001), increased total sleep times (Mbaseline=5.16, SD= 0.63 – MEOT=6.26, SD= 1.23 p<0.001), earlier sleep onsets (Mbaseline=12.26am, SD= 0.05 – MEOT=11.53pm, SD= 0.06 p<0.05), more regular sleep onsets (Mbaseline=0.06, SD= 0.04 – MEOT=0.04, SD= 0.02 p<0.01), a higher sleep regularity index (Mbaseline=44.02, SD= 17.25 – MEOT=55.88, SD= 12.82 p<0.01), and reduced daytime sleepiness (Mbaseline=7.26, SD= 4.30 – MEOT=3.15, SD= 2.46, p<0.001). Conclusion: Extending sleep, as well as improving sleep timing and regularity in racially/ethnically diverse middle-aged short sleepers using a videoconferencing platform is acceptable and feasible. Support (If Any):